Understanding Russian aggression towards Georgia - Michael J. Langlois (Politikon, 2012)
Did Russia initiate conflict with Georgia in an attempt to restrain Georgia from formally joining the Western coalition, or was the decision more complex? What did Russia hope to gain from initiating conflict? What value did Russia assign to maintaining an interest in regional oil trade routes, in which Georgia straddles an important route to the Caspian Sea region? How was the potential incorporation of Georgia into NATO factored into Russia’s decision? To answer these questions, I used the expected-utility model developed by Bruce Bueno de Mesquita. In this analysis, policy preferences and power measurements were considered to determine that Russia’s decision was rationally selected based on a positive expectedutility calculation. I attempted to explain whether this model’s explanatory and predictive capabilities could accurately elucidate Russia’s conflict decision. Furthermore, within the context of the expected-utility model, what can we expect about Russian-Georgian relations in the future?